The Origin and Development of Grounded Theory: A Brief History - henny Suzana Mediani (Jurnal Keperawatan Padjadjaran, 2018)
AbstractGrounded theory is an inductive research method that provides for the systematic generation of theory using qualitative or/and quantitative data generated from interviews, observation, or written sources such as documents, or some combination there of gained by a rigorous research method. Nowadays there has been much used of grounded theory as qualitative methodology in nursing and other health disciplines, Grounded theory has been an important methodology for nursing research. The aim of this brief article is to explain how grounded theory came about.